Association Between Parenting Style and Stunting Among Under-Five Children in the Service Area of Alalak Selatan Community Health Center, Banjarmasin - Devy Sfitri; Rolly Marwan Mathuridy; Linda; Hiryadi (Papua Medicine and Health Science, 2026)
Stunting is a chronic growth disorder among under-five children caused by chronic undernutrition and recurrent infections. Parenting style has been identified as one of the factors associated with stunting. This study aimed to examine the association between parenting style and stunting among under-five children in the service area of Alalak Selatan Community Health Center, Banjarmasin. A descriptive correlational study with a cross-sectional design was conducted among 60 parents of children aged 24–60 months selected using a total sampling technique. Data were collected using a parenting style questionnaire and children's height measurements and were analyzed using Spearman's rank correlation test. Permissive parenting was the most common parenting style (50.0%), and most under-five children were not stunted (72.0%). A significant association was found between parenting style and stunting (p < 0.001; r = 0.598), indicating a moderate correlation. Better parenting practices were associated with a lower risk of stunting. Strengthening parental education on appropriate parenting practices may support stunting prevention.